Participants' use of enacted scenes in research interviews: a method for reflexive analysis in health and social care - James, Deborah M.; Pilnick, Alison; Hall, Alex; Collins, Luke C. (Elsevier, 2016)
In our study of a workforce intervention within a health and social care context we found that participants who took part in longitudinal research interviews were commonly enacting scenes from their work during one-to-one interviews. Scenes were defined as portions of the interviews in which participants directly quoted the speech of at least two actors. Our analysis in this paper focuses on these enacted scenes, and compares the content of them before and after the intervention. We found that, whilst the tensions between consistency and change, and change management, were common topics for scene enactment in both pre and post-intervention data, following the intervention participants were much more likely to present themselves as active agents in that change. Post-intervention enacted scenes also showed participants' reports of taking a service user perspective, and a focus on their interactions with service users that had been absent from pre-intervention data. In addition, descriptions of positive feeling and emotions were present in the post-intervention enacted scenes. We suggest that this analysis confirms the importance of enacted scenes as an analytic resource, and that this importance goes beyond their utility in identifying the impact of this specific intervention. Given the congruence between the themes prominent in enacted scenes, and those which emerged from a more extensive qualitative analysis of these data, we argue that enacted scenes may also be of wider methodological importance. The possibility of using scene enactment as an approach to the validation of inductive analysis in health and social care settings could provide a useful methodological resource in settings where longitudinal ethnographic observation of frontline care staff is impossible or impractical.